Cost Overruns in Hydrocarbon Megaprojects: A Critical Review and Implications for Research - Olaniran, Olugbenda Jide; Love, Peter; Edwards, D.; Olatunji, Oluwole; Matthews, Jane (Project Management Institute, 2015)
Cost overruns are prevalent in hydrocarbon (oil and gas) megaprojects. A recent report indicates that 64% of ongoing megaprojects globally are facing cost overruns. Despite their increasing occurrence, there has been limited published research in the mainstream literature that has specifically examined why and how they occur. Consequently, suggestions regarding how to constructively address cost overruns in hydrocarbon megaprojects are scant. To better understand the causal nature of cost overruns in hydrocarbon megaprojects, this article provides a critical review of the extant literature. Findings from the research indicate that complex interactions between project characteristics, people, technology, and structure and culture contribute to cost overruns occurring. As a result, it is suggested that chaos theory can be used to explain how cost overruns arise in hydrocarbon megaprojects. This article provides a reference point for engendering future research in this pervasive and fertile area.